Injunctions and damages for patent infringement under the UPCA in light of the principle of proportionality - Part I: injunctions - Hofmann, Franz; Raue, Benjamin (Journal of Intellectual Property Law and Practice, 2024)
This article examines the availability of injunctions and the award of damages for patent infringement under the Agreement on a Unified Patent Court, in light of the principle of proportionality. Part I focuses on the injunctive relief and analyses the application of the principle of proportionality to injunctions, outlining key factors and scenarios. Part II, which will be published in the next issue, discusses the principles and methods applicable to the calculation of damages, assessing their suitability in light of the principle of proportionality, as defined in European Union law and in the case law of select contracting states.
CRIS-Team Scopus Importer:2024-06-21